Železni zvonci v Sloveniji - Knific, Timotej (Traditiones (Ljubljana), 1996)
The article deals with 19 iron bells excavated at 14 sites in Slovenia Dating mainly from the Roman period (3th-4th centuries) and the Migration period (5th-6th centuries). Typological characteristics of the bells are described, as well as conditions, analogies and their possible use.
Keywords: archaeology; arheologija; Slovenia; Slovenija; arheološka najdišča; arheološke najdbe; zvonci